Perancangan Aplikasi Mobile Penyetoran Ayat Untuk Mahasiswa Komprehensif di IAIN Bukittinggi Berbasis Android - Wiwit Putriana Sari; Riri Okra (Department of Science and Technology Ibrahimy University, 2020)
This research is motivated by the need for a verse deposit system by students to PA lecturers, students in depositing surah to PA lecturers do not need to carry a deposit card anymore, and do not need to buy into the photo copy building anymore, usually in paragraph deposits students always carry a deposit card every time. want to deposit verses to the PA lecturer, so that sometimes students forget to bring their deposit cards. The purpose of this study was to produce a database of verse deposit storage performed by students to PA lecturers. The type of research used in this research is Research and Development (R&D) research, which is a method used to produce a system, the R&D model used is the 4D version, namely, Define, design, develop, and disseminate, with the system development model using the System Development Life Cycle (SDLC), by applying the waterfall model consisting of, Communication, Planning, Modeling, Construction, and Deployment. Based on the results of the research conducted by the researchers, the researcher succeeded in making a product of the verse deposit system in Iain Bukittinngi. The results of the validity test conducted by computer experts show that this product is very valid with a value of 0.78. The results of the practicality test conducted by PA lecturers showed that this product was declared very practical with a value of 0.96 and the results of the effectiveness test conducted with students showed that this product was very effective with a value of 0.82.